Upcycling waste cement paste powder into a composite cement-free heavy metal stabilization binder - Xiaoliang Fang; Jiefeng Liang; B.A. Mingfang; Minjie Hu; Weihong Xu; Yixin Peng (Environmental Research, 2026)

High-resolution profiling of C10-C20 chlorinated paraffins in seawater and marine organisms: Optimized orbitrap mass spectrometry strategy and bioaccumulation insights from Laizhou Bay, China - Qingkui Cui; Jinzhao Hou; Jia Liu; Deyan Hu; Xiang Yu; Wei Chen; Yuzhu Ding; Yanqing Sun; Mingfang Liu; Yingjiang Xu; Xiaojing Liu; Dianfeng Han (Regional Studies in Marine Science, 2026)

EPDNet: A method for identifying tomato leaf diseases with uneven samples - Zidi Wu; Ding Peng; Mingfang He; Chaoying He; Yang Hu (Computers and Electronics in Agriculture, 2026)

Effectiveness of Salicornia europaea-Derived Biochar in Immobilizing Cadmium in Acidic Soil - Shaoqing Ge; Lei Wang; Mingfang Hu; Zhenyong Zhao; Changyan Tian (Journal of Soil Science and Plant Nutrition, 2025)

AMF: A multi-modal framework for crop leaf diseases segmentation - Yang Hu; Gang Wang; Exian Liu; Jiale Zhu; Mingfang He (Computers and Electronics in Agriculture, 2025)

Homeodomain leucine zipper protein controls the lobed leaf formation by modulating auxin distribution in watermelon - Yimei Zhou; Chuchu Chen; Shiqi Yi; Kejia Zhang; Xiaolong Lyu; Jinghua Yang; Zhongyuan Hu; Mingfang Zhang (Theoretical and Applied Genetics, 2025)

Efficient photoelectrocatalytic simultaneous removal of antibiotic and Cr(VI) upon novel ternary plasma Ag/AgVO3@3D TiO2: Insight into the synergistic mechanism of redox - Yuqing Gao; Yuzhou Jin; Yu Hu; Mingfang Li; Xuejiang Wang; Haiying Ma; Ya-nan Zhang (Chemosphere, 2025)

LVF: A language and vision fusion framework for tomato diseases segmentation - Yang Hu; Jiale Zhu; Guoxiong Zhou; Mingfang He; Mingjie Lv; Junhui Wang; Aibin Chen; Jinsheng Deng; Yichu Jiang (Computers and Electronics in Agriculture, 2024)

Effects of halophyte Suaeda salsa continuous cropping on physical and chemical properties of saline soil under drip irrigation in arid regions - Sihai Liu; Ning Wang; Dongze Li; Changyan Tian; Ke Zhang; Mingfang Hu; Haishan Niu; Zhenyong Zhao (Agriculture, Ecosystems & Environment, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

The safeguard mode of green development in China - Zhengda Li; Yibing Li; Wei Song; Mingfang Dong; Zhihui Yang; Cuili Sun; Xiaomeng Qin; Xiaobing Hu (Environment, Development and Sustainability, 2024)

A large presence/absence variation in the promotor of the ClLOG gene determines trichome elongation in watermelon - Yuyuan Ma; Yu Wang; Zhiqin Zhou; Runqin Zhang; Yiru Xie; Yihan Zhang; Yongming Bo; Xiaolong Lyu; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Theoretical and Applied Genetics, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

A precise apple leaf diseases detection using BCTNet under unconstrained environments - Yukai Zhang; Guoxiong Zhou; Aibin Chen; Mingfang He; Johnny Li; Yahui Hu (Computers and Electronics in Agriculture, 2023)

Allelic variations of ClACO gene improve nitrogen uptake via ethylene-mediated root architecture in watermelon - Kejia Zhang; Wei Gao; Yimei Zhou; Haoshun Zhao; Yuelin Xia; Mengyi Zhang; Yongming Bo; Xiaolong Lyu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Structural variation of GL1 gene determines the trichome formation in Brassica juncea - Yiqing Meng; Xiagolong Lyu; Jiaqi Liu; Wei Gao; Yuyuan Ma; Nanqiao Liao; Zhangping Li; Yongming Bo; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

An allelic variant in the ACS7 gene promotes primary root growth in watermelon - Ahmed Mahmoud; Rui Qi; Haoshun Zhao; Haiyang Yang; Nanqiao Liao; Abid Ali; Guy Kateta Malangisha; Yuyuan Ma; Kejia Zhang; Yimei Zhou; Yuelin Xia; Xiaolong Lyu; et al. (Theoretical and Applied Genetics, 2022)

Nitric oxide alleviates lead toxicity by inhibiting lead translocation and regulating root growth in watermelon seedlings - Jehanzeb Khan; Guy Kateta Malangisha; Abid Ali; Ahmed Mahmoud; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Horticulture, Environment, and Biotechnology, 2021)

Effects of light intensity on Opsin4 , Opsin5, and Pax6 expressions of the sea urchin Strongylocentrotus intermedius - Mingfang Yang; Yushi Yu; Jingyun Ding; Jia Luo; Jiangnan Sun; Fangyuan Hu; Yaqing Chang; Chong Zhao (Marine Ecology, 2020)
The detection of light intensity and subsequent phototaxis are essential for the fitness of sea urchins in intertidal and shallow subtidal waters, where light intensity varies in accordance with the depth and other hydrographic conditions. The molecular basis of photoresponse, however, remains largely unknown. We compared the expression of SiOpsin4 , SiPax6, and SiOpsin5 among tube feet, coelomocytes, gonads, and gut of the sea urchin Strongylocentrotus intermedius . All three genes showed the significantly highest expression in tube feet. To test whether r‐opsin genes (for example, Opsin4 ) and Pax6 in tube feet, rather than chaopsin genes (for example, Opsin5 ), are involved in the molecular responses to light intensity, we investigated the expression of Opsin4 , Pax6, and Opsin5 among four light intensities. Both Opsin4 and Pax6 expressions were significantly higher in the sea urchins at 1,500 lx than at 100, 300, and 700 lx, indicating a co‐upregulation of Opsin4 and Pax6 expressions in sea urchins exposed to the high light intensity (for example, 1,500 lx). However, there was no significant difference of SiOpsin5 expression among the four light intensity groups. Consistent with our hypothesis, there was no significant difference in either Opsin4 or Pax6 expression between the two light intensity environments (low light intensity environment: 50–100 lx; high light intensity environment: 330–1400 lx). This indicates that positive phototaxis and negative phototaxis probably regulate the expression of Opsin4 and Pax6 to a similar level when sea urchins are exposed to the high and low light intensities, respectively. The present study provides new insights into the molecular basis of light intensity detection and subsequent phototaxis of eyeless species.

Evaluating the genetic relationship of Lilium species/cultivars based on target region amplification polymorphism (TRAP) - Yue Hu; Jianwu Ren; Yixin Liu; Mingfang Zhang; The Su Moe; Mohammad Sayyar Khan; Yunpeng Du; Xiuhai Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization of watermelon anther and its programmed cell death-associated events during dehiscence under cold stress - Xiaolong Lyu; Shuna Chen; Nanqiao Liao; Jie Liu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Plant Cell Reports, 2019)

The seedling and cutting propagation techniques of Acer fabri Hance - Bihua Chen; Bin Jiang; Yongsheng Deng; Juan Zhang; Mingfang Hu; Huihua Fan; Xin Li (Vegetos, 2019)

Genome-wide identification and comparative analysis of grafting-responsive mRNA in watermelon grafted onto bottle gourd and squash rootstocks by high-throughput sequencing - Na Liu; Jinghua Yang; Xinxing Fu; Li Zhang; Kai Tang; Kateta Malangisha Guy; Zhongyuan Hu; Shaogui Guo; Yong Xu; Mingfang Zhang (Molecular Genetics and Genomics, 2016)

Advances in research on atmospheric energy propagation and the interactions between different latitudes - Song Yang; Kaiqiang Deng; Mingfang Ting; Chundi Hu (Journal of Meteorological Research, 2015)

Cloning and characterization of HsfA2 from Lily (Lilium longiflorum) - Haibo Xin; Hua Zhang; Li Chen; Xiaoxin Li; Qinglong Lian; Xue Yuan; Xiaoyan Hu; Li Cao; Xiuli He; Mingfang Yi (Plant Cell Reports, 2010)